Curved-crease Cardboard Origami: A Framework for Modular Deployable Cardboard Structures (EAAE Joint Publishings, 2026)
This paper explores the use of curved-creased Origami to create complex architectural forms from corrugated cardboard. Curved-creasing blends folding and bending through curvilinear creases, transforming flat sheets into load-bearing 3D structures. While this technique has been applied to materials like paper, aluminum, and plywood, its potential with cardboard remained unexplored. The study used digital simulations, physical prototyping, and mock-up assemblies to test ten design templates, focusing on minimizing cuts, avoiding wrinkles, and ensuring structural stability. While simulations predicted stress points, physical prototypes revealed that cardboard naturally releases stress through wrinkles along its corrugation channels. To address this, researchers introduced supplementary and stress-releasing fold lines, controlling deformation while enhancing the material’s aesthetic qualities. Findings demonstrate that curved-creased Origami can expand the architectural potential of cardboard, offering a sustainable, low-carbon alternative for design applications.